Effect of Powder Size on Microstructure and Mechanical Properties of 2A12Al Compacts Fabricated by Hot Isostatic Pressing - Xina Huang; Lihui Lang; Gang Wang; Sergei Alexandrov (Advances in Materials Science and Engineering)
This paper studied the effects of powder size on densification, microstructure, and mechanical properties of the hot isostatic-pressed 2A12 aluminum alloy powder compact. The results show that the near-fully dense powder compact can be successfully achieved and the smaller the powder is, the higher the relative density is. In addition, as the powder size decreases, the precipitated phases in the powder compact change from continuously point-like distribution at the junctions among powder particles to the concentrated distribution at the three-way intersections. Compared with the large powder, the tensile strength, yield strength, and elongation of the compact with the small powder were improved by 14%, 30.8%, and 48.6%, respectively.